2020
DOI: 10.1021/acsami.0c07943
|View full text |Cite
|
Sign up to set email alerts
|

Functional Channel of SWCNTs/Cu2O/ZnO NRs/Graphene Hybrid Electrodes for Highly Sensitive Nonenzymatic Glucose Sensors

Abstract: The hybrid electrode of single-wall carbon nanotubes (SWCNTs)/Cu2O/ZnO nanorods (NRs)/graphene used on the current-response nonenzymatic glucose sensor was investigated herein, regarding the mechanism of the formation of functional channel. The synthesis of the hybrid electrode involved four steps. First, the graphene was grown by chemical vapor deposition (CVD) and then wet-transferred onto indium transparent oxide (ITO) glass. Second, a zinc oxide (ZnO) seed layer was sputtered onto the graphene/ITO glass, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…In particular, the sensitivity value is not only superior to that of the binary counterparts (442.2 and 1052.6 µA mm −1 cm −2 for the NiF@GNSs and NiF@Co 3 O 4 NGs, respectively), but also even one to two orders of magnitude higher than the data of other ever reported non-enzymatic sensors for glucose detection (Table 1). [55][56][57][58][59][60][61][62][63][64][65][66] The increase of glucose concentrations causes the decline in the slope of fitting plots since the surface-controlled electrochemical oxidation of glucose is affected by the glucose concentration and the active sites on the surface of catalysts. As the glucose concentration rises, the number of available surface-active sites reduces and thus the increase in rate of currents slows down.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the sensitivity value is not only superior to that of the binary counterparts (442.2 and 1052.6 µA mm −1 cm −2 for the NiF@GNSs and NiF@Co 3 O 4 NGs, respectively), but also even one to two orders of magnitude higher than the data of other ever reported non-enzymatic sensors for glucose detection (Table 1). [55][56][57][58][59][60][61][62][63][64][65][66] The increase of glucose concentrations causes the decline in the slope of fitting plots since the surface-controlled electrochemical oxidation of glucose is affected by the glucose concentration and the active sites on the surface of catalysts. As the glucose concentration rises, the number of available surface-active sites reduces and thus the increase in rate of currents slows down.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of the aforementioned prominent challenges, these main guidelines can provide the ground for identifying the potential new TMO NPs as the viable candidates for replacing the present electrode substances: 1) dimension control synthesis of the TMOhetero-structures for achieving the optimized active sites [182,183], 2) establishing 2D shape of the single or few atomic layers of the transition metal elements through the epitaxial overgrowth of the secondary metals [184], 3) constructing the nano-composites with the carbon nanomaterials like carbon nanotubes (CNTs), activated carbon, graphene and so on to enhance their catalytic activity and conductivity, and attain monodispersivity with lower dimensional NPs [185,186], 4) generating the nanocomposites with other metals to gain higher catalytic activities and sensitivities for diverse sensor platforms [187], 5) understanding basic associations of the morphological structure, dimensions, compositions and catalytic activities of the transition metal/oxide nano-materials [188,189], 6) optimizing the multimetal or oxide nanomaterials for amplification of the catalytic activities, charge storage capacity, and the prolonged stability [190,191], and 7) selecting the substances and designing the new nanocomposites with other materials such as alloys, dopants, and core-shell structures for enhancing the new functionalities, higher conductivity, longer chemical durability, and higher surface areas [192][193][194].…”
Section: Discussionmentioning
confidence: 99%
“…However, the direct growth of graphene onto metallic substrate electrode encloses a possibility the graphene to be contaminated with metallic impurities [ 57 ], influencing its electrochemical and electronic properties. So, different metallic conductive substrates, such as indium tin oxide (ITO), fluorine tin oxide (FTO) [ 58 ] and others have also been studied [ 32 , 59 ].…”
Section: Graphene-based Nanomaterials For Glucose Electrochemical Sensorsmentioning
confidence: 99%
“…Chen et al [ 59 ] reported the direct growth of graphene onto Cu foil via CVD method, its spraying with poly(methyl methacrylate, PMMA) and then the PMMA/graphene transfer (via a wet transference process) onto the ITO. However, we deduce that this synthesis method reintroduces the transfer step that was disregarded according to the direct growth of graphene onto metallic foil.…”
Section: Graphene-based Nanomaterials For Glucose Electrochemical Sensorsmentioning
confidence: 99%